Anagyrine desensitization of peripheral nicotinic acetylcholine receptors. A potential biomarker of quinolizidine alkaloid teratogenesis in cattle. (December 2017) - Green, Benedict T.; Lee, Stephen T.; Welch, Kevin D.; Cook, Daniel
Abstract: Anagyrine, a teratogenic quinolizidine alkaloid found in Lupinus spp., is proposed to undergo metabolism by pregnant cattle to a piperidine alkaloid which inhibits fetal movement, the putative mechanism behind crooked calf syndrome. The objective of this study was to test the hypothesis that anagyrine but not lupanine or sparteine can directly, without metabolism, desensitize nicotinic acetylcholine receptors (nAChR) in a cell culture model. SH-SY5Y cells expressing autonomic nAChR, and TE-671 cells expressing fetal muscle-type nAChR were exposed to lupine alkaloids or Dimethylphenylpiperazinium (DMPP) in log10 molar increments from 10 nM to 100 μM and then to a fixed concentration of acetylcholine (ACh) (10 μM for SH-SY5Y cells and 1 μM for TE-671 cells) and the responses measured with a membrane potential sensing dye to assess nAChR activation and desensitization. The selective ganglionic nAChR agonist DMPP used as a positive control, was a potent activator and desensitizer of nAChR expressed by SH-SY5Y cells. Lupanine was a weak agonist and desensitizer in SH-SY5Y cells and sparteine was without effect. Anagyrine acted as a partial agonist in both cell lines with EC50 values of 4.2 and 231 μM in SH-SY5Y and TE-671 cells, respectively. Anagyrine was a desensitizer of nAChR with DC50 values of 6.9 and 139 μM in SH-SY5Y and TE-671 cells, respectively. These results confirm the hypothesis that anagyrine is a potent and effective desensitizer of nAChR, and that anagyrine can directly, without metabolism, desensitize nAChR. Moreover, serum anagyrine concentrations may be a potential biomarker for lupine teratogenicity in cattle. Highlights: Anagyrine but not lupanine or sparteine can directly, without metabolism, desensitize cholinergic receptors. Anagyrine desensitized cholinergic receptors with DC50 values of 6.9 and 139 µM in SH-SY5Y and TE-671 cells, respectively. Serum anagyrine concentrations may be a biomarker for teratogenicity in cattle grazing on lupine-containing rangelands.